Quality of care for people with multimorbidity: a focus group study with patients and their relatives - Pohontsch, Nadine Janis; Schulze, Josefine; Hoeflich, Charlotte; Glassen, Katharina; Breckner, Amanda; Szecsenyi, Joachim; Lühmann, Dagmar; Scherer, Martin (BMJ open, 2021)
Background Prevalence of people with multimorbidity rises. Multimorbidity constitutes a challenge to the healthcare system, and treatment of patients with multimorbidity is prone to high-quality variations. Currently, no set of quality indicators (QIs) exists to assess quality of care, let alone incorporating the patient perspective. We therefore aim to identify aspects of quality of care relevant to the patients' perspective and match them to a literature-based set of QIs. Methods We conducted eight focus groups with patients with multimorbidity and three focus groups with patients' relatives using a semistructured guide. Data were analysed using Kuckartz's qualitative content analysis. We derived deductive categories from the literature, added inductive categories (new quality aspects) and translated them into QI. Results We created four new QIs based on the quality aspects relevant to patients/relatives. Two QIs (patient education/self-management, regular updates of medication plans) were consented by an expert panel, while two others were not (periodical check-ups, general practitioner-coordinated care). Half of the literature-based QIs, for example, assessment of biopsychosocial support needs, were supported by participants' accounts, while more technical domains regarding assessment and treatment regimens were not addressed in the focus groups. Conclusion We show that focus groups with patients and relatives adding relevant aspects in QI development should be incorporated by default in QI development processes and constitute a reasonable addition to traditional QI development. Our QI set constitutes a framework for assessing the quality of care in the German healthcare system. It will facilitate implementation of treatment standards and increase the use of existing guidelines, hereby helping to reduce overuse, underuse and misuse of healthcare resources in the treatment of patients with multimorbidity.